Association of Sociodemographic, Knowledge, Attitude and Practice with Pediculosis Capitis - Linda Amelia; Chairil Anwar; Wardiansah Wardiansah (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2019)
Introduction : Pediculosis capitis is an infection of scalp and hair in humans caused by infestation of Pediculus humanus capitis and usually extends rapidly in a dense environment such as boarding schools. Aim of study : The aim of this study was to determine the association of students’ sociodemographic, knowledge, attitude and practice with pediculosis capitis in Pondok Pesantren Tahfidzil Qur'an Yayasan Tijarotal Lan Tabur Palembang. Methods : This research was an analytical observational study with a cross sectional design conducted on November 2018. There were 117 samples that had the inclusion criteria and hadn’t exclusion criteria. Data collected from anamnesis, questionnaires and hair examinations of respondents. The results were analyzed using Chi-Square and Logistic Regression. Results : Out of 117 students, 57 students (48.7%) has been found positive pediculosis capitis. Statistical test showed that age (p<0.001), gender (p<0.001), education level (p<0.001), knowledge (p=0.035), attitude (p=0.003) and practice (p =0.043) have significant association to the prevalence of pediculosis capitis. However, there was no significant association between father's education (p=1.000), mother's education (p=0.743), father's job (p=0.314), mother's job (p=1.000) and parents' income (p=1.000) to the prevalence of pediculosis capitis. The results of Multiple Logistic Regression analysis showed that gender, knowledge and practice were the most influential factors to the prevalence of pediculosis capitis (p<0.05) with the probability of 96.7%. Conclusion : There was a significant association between age, gender, education level, knowledge, attitude and practice to the prevalence of pediculosis capitis, and the most dominant variables were gender, knowledge and practice.